Parent / responsible social representations on distance education in the COVID-19 pandemic context (Research, Society and Development, 2020)
Distance education has its own methodology that makes up the teaching-learning process, presenting particularities linked to technology. The objective of this research is to describe the concepts of parents / guardians of students regularly enrolled in basic education about the adoption of distance learning in the context of the COVID-19 pandemic. This study is characterized as qualitative of the exploratory descriptive type, whose methodological basis consists of providing familiarity with the research problem. The present provision is part of a research that aimed to know various aspects related to the adoption of Distance Learning (DE) in basic education during the social context of the COVID-19 pandemic. The survey was conducted between the months of April and May and took place through an electronic form and included a population of 105 participants. The distance learning mode has become exponentially popular in recent years, due to the large investments made in this category. However, a lot could be observed in the answers about the use of beliefs about the adoption of distance learning, where it is emphasized the continuity of prejudiced thoughts in relation to distance learning. More research can be carried out in order to discover issues related to the educational methodology that are in vogue.